Skills in Constructing and Implementing Learning Designs for Preservice Mathematics Teacher at Universitas Samudra - Roni Priyanda; Tatang Herman; Iden Rainal Ihsan; Nishabah Fadhelina; Stevi Natalia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Many preservice mathematic teachers use a learning strategy (a model, method, or approach) that is connected to one or more mathematical abilities when preparing their final projects. This research project examines the use of this tactic through a (quasi) experimental learning approach. Upon selecting a learning approach, some final-year students investigate its impact on enhancing students' mathematical proficiency. Aim of this research is to determine the suitability profile of the final assignment of preservice mathematic teachers at Universitas Samudra between the title and the learning design applied and to find solutions to improve the understanding of preservice mathematic teachers at Universitas Samudra in preparing their final assignments. The results of the praxiological analysis skills in constructing and implementing learning designs for preservice mathematic teachers at Universitas Samudra are: 18,18% hhe learning implementation plan is in accordance with the learning model and is explained in the final assignment discussion, 42,42% the learning implementation plan is in accordance with the learning model but is not explained in the final assignment discussion, and 23,33% The learning implementation plan is not in accordance with the chosen learning model.